Exacerbation of Diabetic Retinopathy following Hypoxia-Inducible Factor-Prolyl Hydroxylase Inhibitor Administration: A Case Report - Nobuaki Ariyoshi; Fumiaki Higashijima; Makiko Wakuta; Tadahiko Ogata; Manami Ohta; Kazuhiro Kimura (Case Reports in Ophthalmology, 2024)
Introduction: Hypoxia-inducible factor-prolyl hydroxylase (HIF-PH) inhibitors, used in the treatment of renal anemia, hold the potential to increase the production of vascular endothelial growth factors. Therefore, HIF-PH inhibitors may exacerbate retinal hemorrhage in diseases such as diabetic retinopathy. Here, we present a case involving the administration of an HIF-PH inhibitor, resulting in the exacerbation of retinal hemorrhage in a patient with diabetic retinopathy. Case Presentation: A 32-year-old man with diabetes mellitus and renal anemia caused by diabetic nephropathy was referred to our department for ophthalmic examination, revealing diabetic retinopathy with scattered retinal hemorrhages, exudates, and diabetic maculopathy in both eyes. Darbepoetin alfa was initially administered and switched to the HIF-PH inhibitor roxadustat on day 74. By day 88, fresh retinal hemorrhage was observed in the right eye. On day 132, the retinal hemorrhage had further worsened, with new preretinal hemorrhage in both eyes. Roxadustat was discontinued, replaced with darbepoetin alfa, resulting in retinal hemorrhage improvement by day 181 (49 days post-roxadustat cessation). On day 201, fundus hemorrhage further improved, optical coherence tomography showed no macular edema or subretinal fluid, and the retina was thinning. Fluorescein angiography showed neovascular vessels, active fluorescein leakage, and extensive avascular areas in both eyes, prompting pan-retinal photocoagulation. Visual acuity remained stable throughout treatment. Conclusion: Patients with advanced diabetic retinopathy taking HIF-PH inhibitors should be aware of retinal hemorrhage exacerbations. If observed, the treatment plan, including discontinuation of the HIF-PH inhibitor or switching to another agent, should be discussed with a diabetologist, nephrologist, and ophthalmologist.